PENDAMPINGAN PENGOLAHAN LIMBAH PETERNAKAN SEBAGAI UPAYA MEWUJUDKAN PERTANIAN BERKELANJUTAN DI DESA MARGOSUKO - Nurfitria, Nia; Sriwulan, Sriwulan; Nuruddin, Abdul Wahid (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service activity was carried out in Margosuko Village, Bancar District, Tuban Regency aims to improve the soft skills and hard skills of farmers group to reduce environmental pollution caused by poorly managed livestock waste. Livestock waste will be processed into solid and liquid organic fertilizers, so it will reduce the dependence on chemical fertilizers through the initiation of independent organic fertilizer production from livestock waste. The implementation method begins with participatory preparation (coordination of farmer groups, preparation of Local Microorganisms (MOL) from mimosa roots, and provision of a compost reactor). The activity then continued with blended learning training for 20 farmers with theoretical material on the impact of waste and simultaneous fermentation practices for 2 weeks. The next stage is 2 months of intensive mentoring to solve technical problems in the field. The successful of the program has seen from the increase in the level of empowerment in managing livestock waste. The indicators used are the level of knowledge and the amount of livestock waste that can be managed. The evaluation results show that there has been an increase level of knowledge regarding cattle farm waste management as seen from the average pretest score which was initially 60.1 to 87.55 in the posttest. Meanwhile, the amount of livestock waste that has been successfully processed on to organic fertilizer is around 30%.